2014
DOI: 10.3144/expresspolymlett.2014.45
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched polysiloxane functionalized graphene oxide for dicyclopentadiene bisphenol dicyanate ester nanocomposites with high performance

Abstract: Abstract.We report an efficient and novel method to functionalize graphene oxide (GO) with hyperbranched polysiloxane and successfully compound them with dicyclopentadiene bisphenol dicyanate ester (DCPDCE) to prepare nanocomposites. X-ray photoelectron spectroscopy (XPS) and Fourier-transform infrared spectra (FT-IR) were employed to examine the surface functionalization of GO. The effects of functionalized GO on the curing reaction, mechanical, dielectric and thermal properties of DCPDCE resin were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…In in situ polymerization, the GO is mixed with monomer units to form a solution. The polymerization reaction takes place in the presence of GO to form a hybrid …”
Section: Introductionmentioning
confidence: 99%
“…In in situ polymerization, the GO is mixed with monomer units to form a solution. The polymerization reaction takes place in the presence of GO to form a hybrid …”
Section: Introductionmentioning
confidence: 99%
“…Figure 11a represents a readily happening hydrolysis process when moisture present in the atmosphere reacts with APTES. In this process, more reactive silanols groups are produced from hydrolysis of ethoxysilanes [27]. Subsequent to formation of silanols, polysiloxane network structure are formed from self-condensation of silanols [28,29].…”
Section: Chemical Mechanism Of Reclaiming and Compatibilizationmentioning
confidence: 99%
“…Therefore, the functionalized GO with HBPSi has better dispersity in the composites and enhanced interfacial adhesion between nanoparticles and resin matrix. Yan's group [21,22] prepared GO functionalized by hyperbranched polysiloxane through hydrosilylation reaction, and incorporated it into cyanate ester (CE) and bismaleimide (BMI) to fabricate nanocomposites. It is found that the mechanical properties, thermal stability, moisture resistance and tribological performance of the nanocomposites are superior to those of neat CE and BMI resin.…”
Section: Introductionmentioning
confidence: 99%